Alternative Lithographic Technologies IV 2012
DOI: 10.1117/12.915803
|View full text |Cite
|
Sign up to set email alerts
|

Zone plate focused soft x-ray lithography for fabrication of nanofluidic devices

Abstract: Sealed nanofluidic channels with cross sections of sub-100 nm * 100 nm were created in a polymer bilayer using the focused soft X-rays of a scanning transmission X-ray microscope and the direct write method. The width of the nanochannels can be controlled by the area patterned in X and Y, while the height can be controlled by tuning the layer thicknesses. Formation of the desired structures has been confirmed by near edge X-ray absorption fine structure spectromicroscopy and scanning electron microscopy. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the best case, OSA-to-sample distances <200 µ m should be aimed for to enable the use of higher resolving Fresnel zone plates and deposition at the C K-edge. Previous experiments on XRL with STXM have shown that the achievable patterning resolution for that approach is in the range of the minimum spot size of the applied Fresnel zone plate [36,37]. In FXBID the mean free path of the occurring secondary electrons is negligible and it is proposed that proximity effects play a minor role.…”
Section: Required Next Stepsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the best case, OSA-to-sample distances <200 µ m should be aimed for to enable the use of higher resolving Fresnel zone plates and deposition at the C K-edge. Previous experiments on XRL with STXM have shown that the achievable patterning resolution for that approach is in the range of the minimum spot size of the applied Fresnel zone plate [36,37]. In FXBID the mean free path of the occurring secondary electrons is negligible and it is proposed that proximity effects play a minor role.…”
Section: Required Next Stepsmentioning
confidence: 99%
“…Furthermore, standard XRL uses relatively large spot sizes and nanostructuring is typically achieved by lithography masks [26][27][28][29][30][31][32]. Very few studies have employed the focused beam of a scanning transmission X-ray microscope (STXM) for maskless direct-write patterning of polymer films [33][34][35][36][37]. Since synchrotron-based X-ray microscopes offer continuously tunable excitation photon energy, it has been shown that within a multilayer of several photoresists consecutively stacked at the same spot, each layer can be addressed separately by the resonant photon energy of the respective Following the development of suitable focusing optics for soft X-rays [49][50][51], the first soft X-ray microscopes were installed in the mid-1980s [52,53].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations